Comprehensive Genomic Characterization Analysis of lncRNAs in Cells With Porcine Delta Coronavirus Infection - Liu, Junli; Wang, Fangfang; Du, Liuyang; Li, Juan; Yu, Tianqi; Jin, Yulan; Yan, Yan; Zhou, Jiyong; Gu, Jinyan (Frontiers in Microbiology, 2020)
Porcine delta coronavirus (PDCoV) is a novel emerging enterocytetropic virus causing diarrhea, vomiting, dehydration, and mortality in suckling piglets. Long non-coding RNAs (lncRNAs) are known to be important regulators during virus infection. Here, we describe a comprehensive transcriptome profile of lncRNA in PDCoV-infected swine testicular (ST) cells. In total, 1,308 annotated and 1,190 novel lncRNA candidate sequences were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that these lncRNAs might be involved in numerous biological processes. Clustering analysis of differentially expressed lncRNAs showed that 454 annotated and 376 novel lncRNAs were regulated after PDCoV infection. Furthermore, we constructed a lncRNA-protein-coding gene co-expression interaction network. The KEGG analysis of the co-expressed genes showed that these differentially expressed lncRNAs were enriched in pathways related to metabolism and TNF signaling. Our study provided comprehensive information about lncRNAs that would be a useful resource for studying the pathogenesis of and designing antiviral therapy for PDCoV infection.